Pengaruh Kreativitas dan Kemandirian Terhadap Minat Berwirausaha (Survey Pada Siswa SMK Swasta di Jakarta Timur) - Intan Lestari; Chandra S. Haratua; Syahid Syahid (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
The aim of this research is to find out: 1). The influence of creativity and independence together on the entrepreneurial interest of private vocational school students in East Jakarta. 2). The influence of creativity on the entrepreneurial interest of private vocational school students in East Jakarta. 3). The influence of independence on the entrepreneurial interest of private vocational school students in East Jakarta. The method used in this research is a survey method with correlational statistical techniques of multiple linear regression with a sample size of 60 students. The research results show: 1) There is a significant influence of creativity and independence together on the entrepreneurial interest of private vocational school students in East Jakarta. This can be proven by the Sig value. 0.00 0.05 and calculated F = 11.603. 2) There is a significant influence of creativity on the entrepreneurial interest of private vocational school students in East Jakarta. This can be proven by the Sig value. 0.048 0.05 and t count 2.081. 3) There is a significant influence of independence on the entrepreneurial interest of private vocational school students in East Jakarta. This can be proven by the Sig value. 0.031 0.05 and t count 2.209.